Nature Images in Novel by G. de Stael “Corinna, or Italy” - T. V. Nuzhnaya (Научный диалог)
The artistic relationships of landscape space and national character in the novel by a French writer of the 19th century G. de Stael are examined. The research urgency is caused by the interest of representatives of different areas of the humanities, including literary critics, to the comparative study of peoples in the context of the rapid development of intercultural communication. It is shown that nature as a whole as “the phenomenon of the poetic image” is of great interest from the point of view of analysis of its impact on the character and emotional state of the characters of the novel. Not less important role plays the analysis of specific natural images of Sun, Moon, Earth, Mountains, Water and Fire that are the deepest archetypes, rooted in the collective unconscious. The author comes to the conclusion that these archaic concepts are reinterpreted by the writer under the influence on the formation of national identity, character and habits of the individual, therefore, it becomes possible for the reader to understand the national mentality through the natural archetypes of the novel. It is shown that in the novel the author creates a verbal-based acceptance of “collateral characteristic of mood,” which will then be actively used in the cinema. It is noted that the functions of the landscape in the novel by the French writer would later become the example for the following generations of authors in the description of the southern Italian landscape.